Phenotypic and functional consequences of different isolation protocols on skin mononuclear phagocytes. Issue 6 (7th March 2017) - Botting, Rachel A; Bertram, Kirstie M; Baharlou, Heeva; Sandgren, Kerrie J; Fletcher, James; Rhodes, Jake W; Rana, Hafsa; Plasto, Toby M; Wang, Xin Maggie; Lim, Jake J K; Barnouti, Laith; Kohout, Mark P; et al.
Abstract : Comparison of skin mononuclear phagocyte isolation techniques on function and subset definition, and the effects of collagenase blends on pathogen binding receptor cleavage. Abstract: Mononuclear phagocytes are present in skin and mucosa and represent one of the first lines of defense against invading pathogens, which they detect via an array of pathogen-binding receptors expressed on their surface. However, their extraction from tissue is difficult, and the isolation technique used has functional consequences on the cells obtained. Here, we compare mononuclear phagocytes isolated from human skin using either enzymatic digestion or spontaneous migration. Cells isolated via enzymatic digestion are in an immature state, and all subsets are easily defined. However, cells isolated by spontaneous migration are in a mature state, and CD141 cross-presenting DCs (cDC1) are more difficult to define. Different pathogen-binding receptors are susceptible to cleavage by blends of collagenase, demonstrating that great care must be taken in choosing the correct enzyme blend to digest tissue if carrying out pathogen-interaction assays. Finally, we have optimized mononuclear phagocyte culture conditions to enhance their survival after liberation from the tissue.